A review of risk-based security and its impact on TSA PreCheck. (29th October 2020) - Albert, Laura A.; Nikolaev, Alexander; Lee, Adrian J.; Fletcher, Kenneth; Jacobson, Sheldon H.
Abstract: Since September 11, 2001, the United States has invested a significant amount of resources into improving aviation security operations, with the Transportation Security Administration (TSA) assuming the responsibilities for security policy-making at commercial airports. This article reviews the literature that supports policies for risk-based passenger screening procedures and chronicles the analytical analysis leading up to the launch (in October 2011) of the TSA Precheck program, as a first step toward implementing a risk-based security strategy for passenger and baggage screening. Multi-level passenger prescreening is the basis of the mathematical framework behind TSA Precheck; the framework provides a prescriptive control of security operations in settings with limited resources. TSA Precheck assigns each passenger to a risk group, based on the initial perceived risk level (assessed in the prescreening stage), and then calibrates the security measures to mitigate the risk associated with each group. With passengers arriving in real-time and the order of their arrivals uncertain, the resource utilization problem is solved by dynamic programming. A numerical comparison between a risk-based and an equal-risk (i.e., non-risk-based) security model is presented to quantify the benefits of risk-based security.